2006
DOI: 10.1159/000091743
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Heat Shock and Hypoxia on Neonatal Neutrophil Lipopolysaccharide Responses: Altered Apoptosis, Toll-Like Receptor-4 and CD11b Expression Compared with Adults

Abstract: Background: Dysfunctional inflammatory responses have been implicated in several neonatal inflammatory disorders following infection and hypoxia. Objectives: We aimed to study the effects of in vitro hypoxia and heat shock (HS) on normal adult and newborn neutrophil migration (CD11b) and persistence (apoptosis) following lipopolysaccharide (LPS) stimulation. Methods: The mechanism for altered LPS responses was assessed at the level of the LPS signalling receptors, Toll-like receptor-4 (TLR-4), TLR-2 and CD14 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
19
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 53 publications
4
19
0
Order By: Relevance
“…In contrast, the synergism between LPS and MV was not present in the juvenile mice, suggesting that important interactions between innate immunity and responses to mechanical stretch in the lungs are acquired with age. These findings are consistent with previous studies in rodents showing that newborns have lesser inflammatory and injury responses to hypoxia, MV, and LPS as compared with adults (13,18,19,33). These data are broadly consistent with clinical observations suggesting that children have a lower incidence and a better outcome from ALI than adults (1, 3).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast, the synergism between LPS and MV was not present in the juvenile mice, suggesting that important interactions between innate immunity and responses to mechanical stretch in the lungs are acquired with age. These findings are consistent with previous studies in rodents showing that newborns have lesser inflammatory and injury responses to hypoxia, MV, and LPS as compared with adults (13,18,19,33). These data are broadly consistent with clinical observations suggesting that children have a lower incidence and a better outcome from ALI than adults (1, 3).…”
Section: Discussionsupporting
confidence: 92%
“…Apoptosis is an important process in normal lung development as well as in lung injury and repair (57,58). B-cell leukemia/lymphoma 2 (Bcl2) and mitogen-activated kinases (MAPK) have been shown to be important in mediating antiinflammatory and antiapoptotic responses to hypo-and hyperoxia, lipopolysaccharide, and mechanical stretch (33,55,(59)(60)(61). Amyloid b-protein precursor (App) has been shown to suppress FE65 (a neural adaptor protein) mediated apoptosis in neurons (62), but the role of this pathway in the lungs is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Increases in maternal blood levels of the complement component C3b, CD11b/CD18 adhesion molecules, and IL-8 receptors are also observed during labor, and these may contribute to decreased neutrophil apoptosis (6). Hypoxia, which can occur transiently during labor, also suppresses neutrophil apoptosis (7)(8)(9). It has been suggested that the antiapoptotic effects of inflammatory mediators and of hypoxia are due, in part, to up-regulation of proteins such as IAP-2, which block the activity of proapoptotic caspases (10).…”
mentioning
confidence: 99%
“…Each sample was acquired over 2 min at medium speed, and a minimum of 5,000 events were collected and analyzed. All measurements were performed under the same instrument settings (39).…”
Section: Quantification Of Intracellular Roi Productionmentioning
confidence: 99%
“…Articles agent LPS 1 μg/ml to mimic an inflammatory response in vitro (39). Samples were analyzed using an Accuri C6 flow cytometer with a CFlow Plus software.…”
mentioning
confidence: 99%